Rice farming profit-sharing: policies, implementation, weaknesses, and improvement efforts - Halim, Abdul; Faisal, Muhammad (Agriekonomika, 2024)
The current practice of profit-sharing in rice farming tends to be unfair and disadvantageous to tenant farmers. This study aims to analyze the policies, implementation, weaknesses, and improvement efforts regarding profit-sharing in rice farming. The researcher employed a qualitative approach with a narrative method. The employed data collection methods comprised interviews, observations, and documentation. Subsequently, the gathered data underwent analysis using Miles and Huberman’s model, encompassing data reduction, visualization, and verification/conclusion. Research findings reveal that profit-sharing arrangements between tenant farmers and landowners are frequently communicated orally, remaining privy solely to the involved parties. Tenant farmers bear the entire burden of production costs and the risk of crop failure, leading to disproportionate profit distribution. Additionally, landowners may unilaterally terminate agreements. To address these issues, written profit-sharing agreements are necessary. The allocation of production costs in farming, including the payment of rice farming insurance (AUTP) premiums to mitigate the risk of crop failure, should be clearly and fairly established, ensuring it does not unduly burden any party involved. In addition, profit distribution should align with contributions. Furthermore, termination of the agreements should not be unilateral and must be in coordination with the local government. Therefore, establishing these aspects within Regional Regulations is crucial for ensuring fair and mutually beneficial profit-sharing practices.